Novel Approaches for Imaging Vascular Development in Mouse Embryos - Berrios-Otero, Cesar A (ProQuest Dissertations & Theses, 2011)
The mouse has become the model organism of choice for developmental studies in mammals. The ability to create targeted mutations and transgene insertions into the mouse genome has enabled a wide variety of experiments that have provided insight into the complex processes that take place during normal mammalian development. In particular a number of experiments using genetically engineered mice has allowed for the identification of molecules necessary for normal mouse cardiovascular development. Although great advancements have been made in the field of mouse genetics, analyzing the three dimensional aspects inherent to such a complex process as cardiovascular development is currently difficult and limits our understanding of both normal cardiovascular development and mutant phenotypes. The use of traditional histological methods are inherently two-dimensional (2D) and reconstructing three-dimensional (3D) images of the vasculature based on these methods is very difficult and seldom ever attempted. Towards a better understanding of the normal patterning of the mouse vasculature I first investigated the use of a gadolinium (Gd) based magnetic resonance imaging (MRI) contrast agent, perfused intravascularly into fixed mouse embryos prior to ex vivo micro-MRI. I have used this technology to analyze wild-type mice as well as mice with mutations that disrupt cardiovascular development. Furthermore in my thesis I describe a method to visualize embryonic vasculature in utero without the need to destructively extract and perfuse embryos, thus allowing for the in vivo analysis of the highly dynamic processes involved in vascular development. Finally with the aim of achieving better contrast between the developing vasculature and the surrounding tissues I co-developed a transgenic mouse for the targeting of contrast agents to the endothelial cells of embryonic blood vessels. These advances now enable in vivo studies of cardiovascular development in mouse embryos, using 3D micro-MR imaging.